(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study investigated the anti-inflammatory, analgesic, and toxicity profiles of different polarity solvent extracts of Vernonia anthelmintica (L.) Willd. (family: Asteraceae) in albino rats and mice. The petroleum ether (VAPE), chloroform (VACE), and hydroalcoholic (VAHA) extracts were evaluated using Carrageenan-induced paw edema (CIPE) and cotton pellet-induced granuloma methods for anti-inflammatory properties, while central and peripheral pain relief activities were assessed using the hot plate and acetic acid-induced writhing test. The study also included toxicological profiling using the Up-and-Down Procedure method. Results showed that VAPE, VACE, and VAHA at a single oral dose of 2000 mg/kg were safe. These extracts demonstrated dose-dependent anti-inflammatory effects, significantly reducing inflammation in CIPE and cotton pellet-induced granuloma models. They also exhibited positive effects on serum and liver tissue biochemical parameters. Moreover, the extracts displayed central and peripheral analgesic effects, as evidenced by increased latency time in the hot plate test and reduced number of writhes induced by acetic acid in a dose-dependent manner. In conclusion, the study highlights the significant dose-dependent anti-inflammatory and analgesic activities of different polarity solvent extracts of V. anthelmintica, with VAHA showing more pronounced effects. Further research is needed to understand the underlying mechanisms of action.